Microsoft Expression Web 4 step by step - Leeds, Chris (Redmond, Wash. : Microsoft ; Sebastopol, CA : O'Reilly [distributor] ; New Delhi : PHI Learning Pvt. Ltd., 2011)
Offers instructions on how to create Web pages and set up new sites with Expression Web.
Keywords: Microsoft Expression Web; Microsoft Expression Web (Computer software); Web sites -- Design; Web sites -- Design